Analysis of Food Quality and Price in Increasing Customer Satisfaction at Anantara Uluwatu Bali Resort - I Ketut Akas Wicaksana; Elvira Septevany; I Nyoman Winia; Ni Gst Nym Suci Murni (Sekolah Vokasi, Universitas Gadjah Mada, 2021)
The purpose of this research was to analyze the effect of food quality, and price in increasing customer satisfaction at Anantara Uluwatu Bali Resort. This research was conducted at Anantara Uluwatu Bali Resort at Botol Biru Bar & Grill using 30 visitors as research samples. The data collection method used a questionnaire and observation, where the data collected was then analyzed using Multiple Linear Regression Analysis. The results showed that the variables of food quality, and price had a positive and significant effect on customer satisfaction at Anantara Uluwatu Bali Resort. Anantara Uluwatu Bali Resort is expected to be able to maintain food quality and prices and be able to improve food quality ranging from variety, appearance, food health, taste, and temperature to food, and to increase prices according to food quality during the pandemic.